Controlling EU agencies : the rule of law in a multi-jurisdictional legal order - Scholten, Miroslava <<[HerausgeberIn]>> (Edward Elgar Publishing, 2020)
"Controlling EU Agencies launches the debate on how to build a comprehensive system of controls in light of the ongoing trends of agencification and Europeanisation of the executive in the EU. Expert multi-disciplinary contributors explore the potential of interconnecting different concepts and types of controls, as well as different outputs of EU agencies, to address the challenges and limitations that individual types of control present. Insightful chapters analyse these issues in relation to individual concepts of control - autonomy, accountability, effective judicial protection, deference, protection of fundamental rights, transparency, liability - as well as specifically for different types of agencies' outputs, including both soft and hard laws. Through the creation of a systemic view, the book suggests ways in which this system of controls may be improved for the future. Timely and engaging, this book will be of great interest to scholars and students of law, governance, public administration and political science, especially those investigating controls of public power. It will also provide an important resource for researchers and officials dealing with design and operation of EU agencies"–
Includes index